Społeczna nauka Kościoła o rozwoju technologicznym na przykładzie genetycznie modyfikowanych organizmów - Panciszko, Barbara (Koło Naukowe Doktryn Politycznych i Prawnych, Katedra Doktryn Politycznych i Prawnych, Wydział Prawa, Administracji i Ekonomii Uniwersytet Wrocławski, 2017)
The purpose of this article is to analyze the approach of the Catholic Church to the problem of technical development in the area of genetic modified organisms and its use that effects in agricultural. Genetic modified organism has been defined and it’s political and economic meaning has been shown. Author analyzed what popes (Paul VI, John Paul II and Benedict XVI) wrote about progress and technical development in their encyclicalsThere have been attempts to synthesize the teaching of the church about GMO based on Pope Francis’ encyclical and selected homily of John Paul II
Keywords: społeczna nauka kościoła; rozwój; postęp technologiczny; genetycznie modyfikowane organizmy